DEEP ANALYSIS OF THE NERVOUS SYSTEM AND NERVE FIBERS - Mamatyokubova Malohat Sharof qizi (International Multidisciplinary Journal for Research & Development, 2024)
The human sensory system is a surprisingly complicated and many-sided organization of specific cells and designs that work as one to facilitate and manage the body's different capabilities. At the core of this framework lie the nerve strands, which act as the essential courses for the transmission of electrical motivations and the trading of data between various pieces of the body. A profound examination of the sensory system and its nerve filaments is vital for understanding the central instruments that support our capacity to see, process, and answer our general surroundings. In this article, we will investigate the arrangement of nerve and its importance in science.